Altered Expression of 3β‐HSD, CYP17 and 17β‐HSD in the Foetal Porcine Gonads in Response to Anti‐androgen Flutamide Exposure. Issue 5 (11th August 2014) - Knapczyk‐Stwora, K; Grzesiak, M; Slomczynska, M
Contents We investigated whether the limited access to androgens during late prenatal period alters expression of steroidogenic enzymes involved in androgen production: 3β‐hydroxysteroid dehydrogenase/Δ5‐Δ4 isomerase (3β‐HSD), cytochrome P450 17α‐hydroxylase/17, 20‐lyase (CYP17) and 17β‐hydroxysteroid dehydrogenase type 1 (17β‐HSD1) or type 3 (17β‐HSD3) in the foetal porcine gonads. Pregnant gilts were injected with anti‐androgen flutamide (for seven days, 50 mg/day/kg bw) or corn oil (control) starting at 83 (GD90) or 101 (GD108) gestational day. To assess 3β‐HSD, CYP17 and 17β‐HSD1 or 17β‐HSD3 expression, real‐time PCR and immunohistochemistry were performed. In testes from flutamide‐treated foetuses, increased 3β‐HSD and CYP17 mRNA expression was observed in the GD90 group, while decreased 3β‐HSD and 17β‐HSD3 mRNA expression and increased CYP17 mRNA expression were found in the GD108 group. CYP17 and 17β‐HSD3 were localized in Leydig cells. Following flutamide administration, the intensity of CYP17 immunostaining was higher in both treated groups, while 17β‐HSD3 intensity was lower in the GD108 group. In ovaries from flutamide‐treated foetuses in the GD90 group, mRNA level for 3β‐HSD was elevated, but it was diminished for CYP17 and 17β‐HSD1. In the GD108 group, flutamide treatment led to lower mRNA level for 3β‐HSD but higher for CYP17. 3β‐HSD was found in granulosa cells, while CYP17 was localized within egg nests and oocytes of forming follicles. Following flutamide treatment, the intensity of 3β‐HSD and CYP17 immunostaining was higher in the GD90 and GD108 groups, respectively. Immunohistochemical staining for 3β‐HSD was restricted to the ovary. Concluding, diminished androgen action in the porcine foetal gonads during late gestation induces changes in steroidogenic enzymes expression, which may led to changes in gonadal function. However, it seems that androgens exert diverse biological effects depending on the gestational period.